Genome-scale comparison of expanded gene families in Plasmodium ovale wallikeri and Plasmodium ovale curtisi with Plasmodium malariae and with other Plasmodium species. Issue 11 (October 2016) - Ansari, Hifzur Rahman; Templeton, Thomas J.; Subudhi, Amit Kumar; Ramaprasad, Abhinay; Tang, Jianxia; Lu, Feng; Naeem, Raeece; Hashish, Yasmeen; Oguike, Mary C.; Benavente, Ernest Diez; Clark, Taane G.; Sutherland, Colin J.; et al.
Graphical abstract: Highlights: We present the draft genomes of Plasmodium ovale wallikeri, Plasmodium ovale curtisi and Plasmodium malariae . Multigene families of P. ovale and P. malariae are compared with those of other Plasmodium spp. Plasmodium ovale and P. malariae genomes are relatively large (∼33 Mb). There is extensive expansion of the pir and surfin gene families in P. ovale spp. We report a new and highly expanded gene family (Pm-fam-a) with transmembrane domain(s) in P. malariae . Abstract: Malaria in humans is caused by six species of Plasmodium parasites, of which the nuclear genome sequences for the two Plasmodium ovale spp., P. ovale curtisi and P. ovale wallikeri, and Plasmodium malariae have not yet been analyzed. Here we present an analysis of the nuclear genome sequences of these three parasites, and describe gene family expansions therein. Plasmodium ovale curtisi and P. ovale wallikeri are genetically distinct but morphologically indistinguishable and have sympatric ranges through the tropics of Africa, Asia and Oceania. Both P. ovale spp. show expansion of the surfin variant gene family, and an amplification of the Plasmodium interspersed repeat ( pir ) superfamily which results in an approximately 30% increase in genome size. For comparison, we have also analyzed the draft nuclear genome of P. malariae, a malaria parasite causing mild malaria symptoms with a quartan life cycle, long-term chronic infections, and wide geographic distribution. Plasmodium malariae shows only a moderate level of expansion of pir genes, and unique expansions of a highly diverged transmembrane protein family with over 550 members and the gamete P25/27 gene family. The observed diversity in the P. ovale wallikeri and P. ovale curtisi surface antigens, combined with their phylogenetic separation, supports consideration that the two parasites be given species status.